Energy management in biodiesel production - Klazly, Mohamad Mehi Alddin; Aliyu, Ruwaidu; Sapit, Azwan; Khalid, Amir (Penerbit UTHM, 2020)
Biodiesel economics revolves around both private and public features. Success for an incentive for producers and consumers needs to be sufficient to take part in the marketing arena with the currently accessible alternatives in the private dimension. “Whereas in the civic aspect, success is described in terms of the community objectives that prompt government’s intercession (i. e. subsidies) and whether biodiesel will attain the public goals in a remunerative manner compared to other alternatives if the public assessment is highly preferred, but the market incentives are deficient, there will not be a possibility to produce the biodiesel. On the other hand, if market values generate strong dividends among producers and purchaser, but the social gains are very small, or the costs are extremely high compared to other alternatives, then the activity may not represent a better use of scarce public resources. Biodiesel has become more enticing to the world recently due to its environmental benefits and the fact that it is made from renewable resources. The production cost of biodiesel is the main barrier to commercialization of the product. In the absence of tax relief, there is an urgent need to explore alternative feedstocks for the production of biodiesel. Furthermore, Properties impact of biodiesel and its feedstock, Engine type and its operating conditions Additives are effected by the biodiesel type and production characteristics. Where Engine power is always affected by properties of biodiesel, especially in heating value, viscosity, and lubricity.